Correlation between Short-Form 36 Scores and Neck Disability Index in Patients Undergoing Anterior Cervical Discectomy and Fusion - Ko, Sangbong (Asian Spine J, 2018)
STUDY DESIGN: Case control study. PURPOSE: To determine how the Neck Disability Index (NDI), a cervical spine-specific outcome, reflects health-related quality-of-life, and if NDI is correlated to the 36-item Short-Form Health Survey (SF-36) scores. OVERVIEW OF LITERATURE: NDI is a useful tool for assessing health-related quality of life in patients with neck pain. METHODS: We used the Pearson product-moment correlation coefficient to assess the validity of all items under NDI and SF-36, and the Pearson’s correlation coefficient to assess the correlation between NDI and total SF-36 scores. The primary outcome measures were spine-specific health status- and general health status-measures after spine surgery, and these were evaluated every year for 2 years, using both NDI and SF-36 scores. RESULTS: NDI had a strong linear correlation with SF-36 and its two scales, the Physical Component Score (PCS) and the Mental Component Score (MCS), attesting to the validity of these two instruments. Among the eight subscales of SF-36, there was a strong linear correlation between NDI and PCS-physical functioning, PCS-bodily pain, and MCS-role emotional. Further, a moderate linear correlation was observed between NDI and subscales of PCS-role physical, PCS-general health, and MCS-social functioning, and between NDI and MCS-vitality and MCS-mental health. CONCLUSIONS: Our findings suggest that the NDI adequately reflects the patient’s physical and mental quality of life, implying that the use of NDI to assess functional outcomes can also be ultimately used to evaluate the patient’s quality of life.